Screening for HIV-1 antibodies in pregnancy: results from the Swedish national programme. Issue 6917 (4th December 1993) - Lindgren, S; Bohlin, A B; Forsgren, M; Arneborn, M; Ottenblad, C; Lidman, K; Anzén, B; von Sydow, M; Böttiger, M
Abstract : OBJECTIVE--To determine the effectiveness of a national screening programme for HIV infection in pregnant women. DESIGN--Observational study. SUBJECTS--All pregnant women presenting to antenatal or abortion clinics. SETTING--Sweden, September 1987 to December 1991. MAIN OUTCOME MEASURES--Number and characteristics of infected women. RESULTS--By the end of the study period 510, 000 tests had been performed and 54 women with HIV infection identified (1.06/10, 000). Of the 33 women identified in Stockholm, 14 women (4.4/10, 000) had attended abortion clinics and 19 antenatal clinics (1.8/10, 000; p < 0.05). Three women had been intravenous drug users, one was infected through a blood transfusion, and 50 were probably infected sexually. Of the 20 women who attended antenatal clinics early enough to allow an abortion, 12 continued with their pregnancies. CONCLUSIONS--Testing of all women, not just those perceived to be at risk, probably contributed to the high uptake of HIV testing. With high uptake such screening provides valuable data on spread of HIV in the heterosexual population and presents opportunity for preventing transmission of HIV to children and partners.